Patient trajectories and their impact on mobility, social participation and quality of life in patients with vertigo/dizziness/balance disorders and osteoarthritis (MobilE-TRA): study protocol of an observational, practice-based cohort study. Issue 4 (21st April 2018) - Kisch, Rebecca; Bergmann, Antje; Koller, Daniela; Leidl, Reiner; Mansmann, Ulrich; Mueller, Martin; Sanftenberg, Linda; Schelling, Joerg; Sundmacher, Leonie; Voigt, Karen; Grill, Eva
Abstract : Introduction: Mobility limitations have a multitude of different negative consequences on elderly patients including decreasing opportunities for social participation, increasing the risk for morbidity and mortality. However, current healthcare has several shortcomings regarding mobility sustainment of older adults, namely a narrow focus on the underlying pathology, fragmentation of care across services and health professions and deficiencies in personalising care based on patients' needs and experiences. A tailored healthcare strategy targeted at mobility of older adults is still missing. Objective: The objective is to develop multiprofessional care pathways targeted at mobility sustainment and social participation in patients with vertigo/dizziness/balance disorders (VDB) and osteoarthritis (OA) . Methods: Data regarding quality of life, mobility limitation, pain, stiffness and physical function is collected in a longitudinal observational study between 2017 and 2019. General practitioners (GPs) recruit their patients with VDB or OA. Patients who visited their GP in the last quarter will be identified in the practice software based on VDB and OA-related International Classification of Diseases 10th Revision. Study material will be sent from the practice to patients by mail. Six months and 12 months after baseline, all patients will receive a mail directly from the study team containing the follow-up questionnaire. GPs fill out questionnaires regarding patient diagnostics, therapy and referrals. Ethics and dissemination: The study was approved by the ethical committee of the Ludwig-Maximilians-Universität München and of the Technische Universität Dresden. Results will be published in scientific, peer-reviewed journals and at national and international conferences. Results will be disseminated via newsletters, the project website and a regional conference for representatives of local and national authorities.